Global Stability of an SEIS Epidemic Model with General Saturation Incidence. (11th April 2013) - Zhang, Hui; Yingqi, Li; Xu, Wenxiong
Abstract : We present an SEIS epidemic model with infective force in both latent period and infected period, which has different general saturation incidence rates. It is shown that the global dynamics are completely determined by the basic reproductive number R 0 . If R 0 ≤ 1, the disease-free equilibrium is globally asymptotically stable in T by LaSalle's Invariance Principle, and the disease dies out. Moreover, using the method of autonomous convergence theorem, we obtain that the unique epidemic equilibrium is globally asymptotically stable in T 0, and the disease spreads to be endemic.